Pengaruh Progressive Muscle Relaxation Terhadap Skala Nyeri pada Pasien Post Sectio Caesaria - Asri Wiwi Marwati; Cucu Rokayah; Yeti Herawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Banyaknya ibu post section dapat menimbulkan masalah pada luka sayatan di area abdomen yaitu nyeri. Ibu paska operasi Sectio Caesaria merasakan nyeri yang lebih tinggi dibandingkan dengan persalinan secara pervaginam sehingga kebutuhan ibu akan mobilisasi, perawatan diri dan bayinya, serta pemberian ASI kerapkali terganggu. Penelitian ini bertujuan untuk mengetahui pengaruh Progressive Muscle Relaxation (PMR) terhadap skala nyeri pada pasien post sectio caesaria di RSKIA Kota Bandung. Jenis penelitian ini berupa quasi eksperimen dengan metode pre test dan post test. Populasi penelitian sebanyak 34 pasien dibagi menjadi dua kelompok yaitu kelompok kontrol dan intervensi masing-masing 17 pasien. Metode pengumpulan data dengan carapurposive sampling. Instrumen penelitian ini menggunakan skala NRS (Numeric Rating Scale). Hasil penelitian menunjukkan skala nyeri sebelum dilakukan teknik PMR pada kelompok kontrol berada pada tingkat nyeri sedang sebanyak 7 responden (41.2%) dan pada kelompok intervensi berada pada tingkat sedang sebanyak 14 orang (82.4%). Skala nyeri sesudah dilakukan teknik PMR pada kelompok kontrol berada pada tingkat nyeri sedang sebanyak 10 orang (58.8%) dan pada kelompok intervensi pada tingkat sedang sebanyak 11 orang (64.7%).Pengaruh PMR pada kelompok kontrol memiliki nilai p-value 0.059. Pengaruh teknik PMR pada kelompok intervensi memiliki nilai p-value 0.001 sehingga terdapat pengaruh Progressive Muscle Relaxation pada pasien post sectio caesaria di RSKIA Kota Bandung. Pengaruh teknik PMR terhadap skala nyeri memiliki nilai p-value 0.030 sehingga dapat disimpulkan terdapat pengaruh Progressive Muscle Relaxation pada pasien post section caesaria di RSKIA Kota Bandung. Kata kunci: nyeri, progressive muscle relaxation, sectio caesaria THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION ON THE SCALE OF PAIN IN POST SECTIO CAESARIA ABSTRACTSection caesare caused by problems in wound incisions in the abdominal area, namely pain. Respondent with section caesaria has a higher pain scale compared to respondents with normal delivery, so that the mother's need for mobilization, self-care and her baby, and breastfeeding are often disrupted. This study aims to determine the effect of Progressive Muscle Relaxation (PMR) on the scale of pain in post sectio caesaria patients at RSKIA in Bandung. This type of research is quasi-experimental. The study population was 34 patients divided into two groups, namely the control and intervention groups. This type of research is quasi-experimental with the pre-test and post-test methods. The instrument of this study uses the NRS (Numeric Rating Scale).The results showed the scale of pain before the PMR technique in the control group was at the level of moderate pain as many as 7 respondents (41.2%) and the intervention group was at a moderate level of 14 people (82.4%). The scale of pain after the PMR technique in the control group was at a moderate level of pain of 10 people (58.8%) and in the intervention group at a moderate level of 11 people (64.7%). The effect of PMR techniques on the control group has a p-value of 0.059. The effect of PMR technique on the intervention group has a p-value of 0.001 so that there is an effect of Progressive Muscle Relaxation in post sectio caesaria patients at RSKIA Bandung City. The effect of PMR technique on pain scale has a p-value of 0.030 so it can be concluded that there is an effect of Progressive Muscle Relaxation in post sectio caesaria patients at RSKIA Bandung City.It is hoped that the results of this study can be used as guidelines for nurses' interventions that can be taught to patients and families as a patient companion in conducting this PMR technique. Keywords: pain, progressive muscle relaxation, sectio caesaria